2017
DOI: 10.1002/ecs2.1925
|View full text |Cite
|
Sign up to set email alerts
|

Zebra migration strategies and anthrax in Etosha National Park, Namibia

Abstract: Partial seasonal migration is ubiquitous in many species. We documented this phenomenon in plains zebra (Equus burchelli) in Etosha National Park, Namibia (ENP), and provided a cost-benefit analysis as it relates to the spatial distribution of water, vegetation and endemic anthrax. This analysis draws upon two years of ENP zebra movement data that reveal two sub-populations: migrators and non-migrators. Migrators are shown to be behaviorally dominant in the way they utilize space and use water holes. We raise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…For example, in an anthrax‐endemic region of Namibia, zebra ( Equus quagga ) demonstrate a pattern of partial migration, where dominant herds appear to migrate away from high‐quality habitat during the anthrax season, leaving behind lower‐ranking resident herds to graze despite the higher disease risk (Zidon et al . ). Researchers posing questions solely about movement (why would zebra migrate away from high quality habitat?)…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, in an anthrax‐endemic region of Namibia, zebra ( Equus quagga ) demonstrate a pattern of partial migration, where dominant herds appear to migrate away from high‐quality habitat during the anthrax season, leaving behind lower‐ranking resident herds to graze despite the higher disease risk (Zidon et al . ). Researchers posing questions solely about movement (why would zebra migrate away from high quality habitat?)…”
Section: Introductionmentioning
confidence: 97%
“…In practice, animal movement is driven by decisions that balance this trade-off between habitat quality and disease risk, and behavioural polymorphisms might even evolve as a consequence (Getz et al 2015). For example, in an anthrax-endemic region of Namibia, zebra (Equus quagga) demonstrate a pattern of partial migration, where dominant herds appear to migrate away from high-quality habitat during the anthrax season, leaving behind lower-ranking resident herds to graze despite the higher disease risk (Zidon et al 2017). Researchers posing questions solely about movement (why would zebra migrate away from high quality habitat?)…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, interspecific variation in movement still requires investigation, given the wealth of movement data collected in Etosha over the past two decades (Lyons, Turner & Getz, 2013;Mashintonio et al, 2014;Polansky, Kilian & Wittemyer, 2015;Dougherty et al, 2017Dougherty et al, , 2018aZidon et al, 2017); for example, elephants largely migrate away from the known anthrax areas of Etosha during the anthrax season, and return in the dry season. Intraspecific variation also requires further investigation; evidence suggests that there may be a link between partial migration of zebra herds in Etosha and avoidance of the anthrax season.…”
Section: (4) Ecologymentioning
confidence: 99%
“…Intraspecific variation also requires further investigation; evidence suggests that there may be a link between partial migration of zebra herds in Etosha and avoidance of the anthrax season. It has been suggested that this phenomenon could be linked to dominance structure, as dominant groups migrate, while resident (submissive) herds are encouraged to stay by decreased competition (Zidon et al, 2017). Movement data from Etosha has already been used to help develop anthrax-relevant analytic tools (Dougherty et al, 2017) and simulations (Dougherty et al, 2018a), and while some work in other systems has used movement data and tools to help map the link between environmental suitability and host exposure (Morris et al, 2016), similar work is still needed in Etosha [as it is needed in any system with the potential for transmission at the wildlife-livestock interface, where these tools are often the most useful for answering applied questions (Dougherty et al, 2018b)].…”
Section: (4) Ecologymentioning
confidence: 99%
“…It has been suggested that this phenomenon could be linked to dominance structure, as dominant groups migrate, while resident (submissive) herds are encouraged to stay by decreased competition. 123 Movement data from Etosha has already been used to help develop anthrax-relevant analytic tools 122 and simulations 121 , and while some work in other systems has used movement data and tools to help map the link between environmental suitability and host exposure 127 , similar work is still needed in Etosha (as it is needed in any system with the potential for transmission at the wildlife-livestock interface, where these tools are often the most useful for answering applied questions 128 ).…”
Section: Anthrax: a Case Study In Slow Integrationmentioning
confidence: 99%